Contrasting roles of clouds as a sink and source of aerosols: A quantitative assessment using WRF-Chem over East Asia. (15th May 2022) - Ryu, Young-Hee; Min, Seung-Ki; Knote, Christoph
Abstract: Clouds play two contrasting roles in the fate of aerosols as a sink through wet scavenging and a source as a medium for aqueous-phase secondary aerosol formation. The contrasting contributions of clouds to near-surface particulate matter with a diameter less than 2.5 μm (PM2.5 ) are quantitatively examined with a particular focus on boundary-layer aerosols and clouds using the Weather Research and Forecasting model coupled with chemistry (WRF-Chem). Overall, the net contribution of wet scavenging to daily-mean PM2.5 is much larger (−5 μg m −3 to −22 μg m −3 ) than that of cloud chemistry (∼0.9 μg m −3 ). The effects of wet scavenging are found over a large spatial extent even over no-rainy regions and last for a long time (∼2 days). The amount of aerosols scavenged by clouds and rainfall varies greatly, but it increases as the liquid water path (LWP) increases in a general sense. So, aerosols are mostly removed when clouds have large LWPs. For thin clouds with LWPs of 30–80 g m −2, the net reduction in PM2.5 due to wet scavenging is barely sensitive to LWP and the role of cloud chemistry becomes non-negligible. A relatively large increase in sulfate mass is found when cloud base height (CBH) is lower than ∼1.2 km for thin clouds, and the occurrence fraction in which cloud chemistry plays a dominant role over wet scavenging increases up to ∼30% as CBH becomes lower. These results highlight that fog and/or non-precipitating stratus clouds likely play a substantial role in the formation of aqueous-phase secondary aerosols. A case study reveals that the presence of fog can contribute to increasing sulfate formation at a maximum rate of 1.5 μg m −3 h −1 . Highlights: The effect of wet scavenging by clouds is overall much larger than cloud chemistry. But low-level thin clouds have increased chances of forming secondary aerosols. The presence of fog increases sulfate formation up to a rate of 1.5 μg m −3 h −1 .